The Inframerah untuk Kesembuhan Investigasi Terapi Terhadap Penyembuhan Luka Insisi dalam Konteks Ilmu Kesehatan - Rianti, Emilia Devi Dwi; Simamora, Dorta; Ama, Fuad (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2024)
Currently, alternative therapies are widely used with the aim of reducing pain, swelling and increasing blood circulation. Infrared rays are used in research as a therapy for healing incisional wounds because infrared can penetrate cells or tissue more deeply. Infrared rays in research as a therapy for healing incisional wounds. The experimental animal samples were 24 male Wistar rats treated with K (-) without infrared therapy, P1 was given infrared exposure at a distance of 24 cm and for 20 minutes. P2 was given infrared exposure at a distance of 16 cm and a time of 20 minutes and P3 was given infrared exposure at a distance of 7 cm and a time of 20 minutes. The results showed that the 12th day change in wound healing occurred in the control group = 0.1 cm; P1= 0.2 cm; P2 = 0.4 cm and P3 = 0.5 cm. The conclusion of the research was that effective infrared therapy was shown in treatment group 1 (P1) with an exposure distance of ± 24 cm, because infrared radiation entered the subcutaneous tissue without excessive stimulation or heating